The Audio-Visual Media on Cognitive Learning Outcomes - Wanda Manulang; Haifaturrahmah; Linda Sekar Utami; Syaharuddin; Siti Ala (Jurnal Ilmiah Sekolah Dasar, 2023)
Suitable media in the learning process is required to improve students' cognitive learning outcomes. Utilizing visual and audio media is precise in enhancing students' learning outcomes. This study aims to re-analyze previous studies on the accuracy levels of the effect of students' cognitive learning outcomes in using audio-visual media. The method used in this research is Meta-analysis. The data was acquired from indexing databases such as Google Scholar, Doaj, and Scopus. Afterward, the study conducted data filtration on the research result that contains Fisher test score (F), student test (t), correlation test (r), and the number of students (N). The result of data analysis using JASP software is that as many as 49 data significantly improve students' cognitive learning outcomes using audio-visual media. In data analysis at the elementary school level, the effect is 72%; at the junior high school level, the effect is 77%; and at the senior high school level, the effect is 92%. Then, in the classification of social and cultural subjects, the effect is 82%, while in science and mathematics subjects, the effect is 68%. From comparing the accuracy level of the impact, one can observe that using audio-visual media has an enormous influence at the high school level and on social and cultural subject classification.